Sermons in Stones. Argument and Artefact for Sustainability - Walker, Stuart (Les ateliers de l'éthique / The Ethics Forum, 2010)
The focus of the study is on the values, priorities and arguments needed to advance ‘design for sustainability’. The discussion critiques conventions related to innovation and technology and offers a product design approach that emphasises minimal intervention, integrated thinking-and-doing, reinstating the familiar, localization and the particularities of place. These interdependent themes are discussed in terms of their relationship to design for sustainability and are clarified through the conceptualization, design, production and use of a simple functional object that is, essentially, a ‘symbolic sustainable artefact’. Although it is fully functional, its practical usefulness in contemporary society would probably be seen as marginal. Its potential contribution is as a symbol of an alternative direction. It asks us to consider aspects of our humanity that are beyond instrumental approaches. It challenges sustainable initiatives that become so caught up in practical and environmental concerns that they fail to question the underlying values, priorities and social drivers which affect how we act in the world; those behaviours and norms that have created the very problems we are so urgently trying to tackle. The discussion is accompanied by a parallel series of photographs that document the relationship between argument, locale and the creation of the conceptual artefact. These photographs convey some of the qualitative differences between the place of much contemporary artefact acquisition, i.e. the shopping mall, and the particular locale that yielded the artefact created during this study; they are also useful in conveying the potential relationship that exist between place and the aesthetics of functional objects.